2013
DOI: 10.1007/s00068-013-0268-4
|View full text |Cite
|
Sign up to set email alerts
|

Contralateral extraaxial hematomas after urgent neurosurgery of a mass lesion in patients with traumatic brain injury

Abstract: Contralateral extraaxial hematoma is a rare entity, although it has a high mortality rate. Therefore, it requires a high index of suspicion, especially in patients with severe TBI, with minimal contralateral injury and mainly with contralateral skull fracture on the initial CT scan.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 20 publications
0
5
0
1
Order By: Relevance
“…In the previous studies, certain predictors of postoperative EDH have been reported, the most important of which is the presence of skull fractures [ Table 2 ]. [ 4 , 5 , 8 , 10 , 13 , 15 , 17 - 19 ] Most commonly, the hematoma occurs on the contralateral calvarium, usually with an overlying fracture, the most consistent finding. A younger age, probably related to easiness of dural stripping, and fractures involving multiple calvarial bone plates are identified as independent risk factors in the presence of fractures.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In the previous studies, certain predictors of postoperative EDH have been reported, the most important of which is the presence of skull fractures [ Table 2 ]. [ 4 , 5 , 8 , 10 , 13 , 15 , 17 - 19 ] Most commonly, the hematoma occurs on the contralateral calvarium, usually with an overlying fracture, the most consistent finding. A younger age, probably related to easiness of dural stripping, and fractures involving multiple calvarial bone plates are identified as independent risk factors in the presence of fractures.…”
Section: Discussionmentioning
confidence: 99%
“…The other viable option which allows early detection of the hematomas is performing an ultrasound intraoperatively in susceptible patients such as those with persistent brain bulge. [ 5 ] Given the fact that patients operated for severe TBI are invariably shifted unreversed and electively ventilated, as part of ICP reduction measures in many centers, we prefer obtaining routine immediate postoperative CT scans in these patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The occurrence of extradural hematoma (EDH), following DC for SDH, is rare with about 50 reported cases. [ 1 2 3 4 5 6 7 8 9 10 11 ] We report two cases of EDH, one developing ipsilateral and the other contralateral, following DC and evacuation of SDH. The differences in clinical presentation, pathogenesis, image findings, and outcomes are highlighted.…”
Section: Introductionmentioning
confidence: 99%